REVITALISASI NILAI SUSILA HINDU SEBAGAI BASIS PENDIDIKAN KARAKTER DI TENGAH KRISIS MORAL GENERASI DIGITAL - I Putu Agus Putra Antara (Cangkal : Jurnal Ilmu Sosial Dan Humaniora, 2026)
This study aims to analyze the revitalization of Hindu ethical values (susila) as the foundation of character education amid the moral crisis of the digital generation. The development of digital technology has significantly transformed social life, particularly among young people, as reflected in increasing individualism, degradation of communication ethics, declining social empathy, and weakening moral and spiritual awareness. This research employed a qualitative approach with a descriptive-interpretative design through library research. Data were collected from various scholarly sources, including books, journals, academic articles, and relevant documents related to character education, Hindu ethics, and digital culture. Data analysis was conducted qualitatively through data reduction, data presentation, and interpretative conclusion drawing. The findings reveal that Hindu ethical values such as Tri Kaya Parisudha, Tat Twam Asi, Ahimsa, and Dharma have strong relevance as the foundation of character education for the digital generation. The revitalization of Hindu ethical values can be implemented through the integration of ethical values in education, strengthening morality-based digital literacy, developing educational content on social media, and promoting exemplary conduct in social life. This study emphasizes that character education based on Hindu ethical values functions not only as an effort to preserve religious and cultural values but also as a transformational solution to address the moral crisis in modern digital society.